Sensitive and specific enzymatic assay for the determination of precursor forms of prostate-specific antigen after an activation step. - Niemelä, P; Lövgren, J; Karp, M; Lilja, H; Pettersson, K (2002)
BACKGROUND: The proteome of the serine protease prostate-specific antigen (PSA) and its enzymatic properties have been clarified only recently. We have developed a specific and sensitive method for the measurement of active PSA and used it to measure proPSA in blood. METHODS: We used the synthetic peptide KGISSQY, which possesses a PSA-specific cleavage site, as substrate. To ascertain the specificity of the assay, we used an anti-PSA monoclonal antibody that captures known forms of PSA. An activation step enabled us to measure proPSA by converting it to mature, active PSA. RESULTS: The detection limit of the optimized assay was 0.5 microg/L. In blood samples from patients, the activation step substantially increased the concentration of active PSA, thus showing the presence of proPSA in the samples. ProPSA was 0-79% (median, 45%) of the amount of free PSA in 15 samples with total PSA concentrations of 5.3-423 microg/L. In samples obtained from three benign prostatic hyperplasia (BPH) patients after transurethal resection of the prostate, no significant increase in activity was detected after the activation step, thus showing that proPSA was not a portion of free PSA in plasma of BPH patients. CONCLUSIONS: Proforms of PSA are a considerable fraction of free PSA in the blood of patients with increased total PSA. The approach described can be used to study the diagnostic value of proPSA and active PSA in patients with BPH and prostate cancer.